Why Do Students Need to Establish Ecoliteracy? - Eddy Noviana; Supentri Supentri; Rahmatul Hidayati; Muhammad Nailu Huda (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This survey research aimed at determining the ecological intelligence level ofstudents. It involved 120 fourth grade students of elementary school. Thefindings revealed that the students‟ intelligence level, with an average score of77.48, was classified in „high‟ category. In addition, other aspects were alsoclassified into the „high‟ category with an average score on attitude aspect of78.19, skill aspect of 77.69, and participation aspect of 76.56. To conclude, theecological intelligence of the fourth grade elementary school students wasclassified in „high‟ category.